Modelling steady-state convective heat transfer in different periodic open cellular structures (POCS) – A superposition approach. (January 2023) - Dubil, Konrad; Wetzel, Thomas; Dietrich, Benjamin
Highlights: The convective heat transfer during laminar, steady-state flow in POCS with four different unit cell types is investigated. Fluid deflection is a key factor to understand the convective heat transfer. The heat transfer capability of POCS is relatable to the strut arrangements of which they are composed. A physically founded model for the calculation of the convective heat transfer in POCS with arbitrary unit cell geometries is established, which is valid for porosities above 79.1%. Abstract: Additively manufactured periodic open cellular structures (POCS) offer promising attributes for the intensification of heat transfer processes. Their geometry and consequently thermal transport properties are highly customizable resulting in a vast design freedom. To fully exploit their potential, a detailed understanding of the relationship between their geometric and thermal transport properties is crucial. Therefore, in this contribution the convective heat transfer in four different unit cell geometries and varying cell dimensions during fully developed laminar steady-state flow is investigated. Numerical simulations are used to get a detailed insight of the local flow structures and heat flux density distributions. A correlation between the heat transfer coefficient of each unit cell and the heat transfer capability of unconnected strut arrangements with similar flow paths is introduced. On this basis, a new modelling approach is established in combination with the concept of superposition. It takes into account the detailed geometry of the porous medium and shows good agreement with the simulation data of all unit cell geometries studied in this work with porosities above 79.1%. Thus, it is the first model applicable to different types of unit cells.